Lao People’s Democratic Republic’s Dependency on China’s Infrastructure Assistance - Wiranata Kusuma, Sigit Candra; Winata Bachtiar, Jefferson (WILAYAH: The International Journal of East Asian Studies, 2020)
Despite an acrimonious history, being involved in the second and third Indochina War, in the past few years, Lao People’s Democratic Republic (PDR) seems to have deepened its relations with China. The improvement of friendly bilateral ties between Beijing and Vientiane can be observed by the evidence of China as the largest foreign investor in the country. On one hand, Lao PDR’s struggle to improve its economic its landlocked geography and the need for infrastructure assistance naturally makes the country lean more towards China. On the other hand, Beijing needs Lao PDR’s geographical advantages to complete the Belt and Road Initiative (BRI) project. The objective of this paper is to analyze the evolving relationship between China and Lao PDR within the context of the BRI. This paper concludes that both parties have developed a complex interdependent relationship with China attempting to establish a solid geo-economics system while trying to assert its position in a structural power system. The act of assertion is supported by its foreign policy that is predicted to be utilized to cajole Southeast Asia countries to be part of a community of common destiny under the leadership of Beijing.